2006
DOI: 10.1111/j.1365-2559.2006.02545.x
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate colitis: definition, diagnosis, implications and a plea for nosological sanity

Abstract: In 1978, Price introduced the concept of indeterminate colitis to describe cases in which colonic resections had been undertaken for chronic inflammatory bowel disease (CIBD), but a definitive diagnosis of either of the classical types of CIBD, ulcerative colitis and Crohn's disease, was not possible. This was especially apposite in cases of acute fulminant disease of the colorectum. More recently, the term indeterminate colitis has been applied to biopsy material, when it has not been possible to differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 110 publications
3
30
0
Order By: Relevance
“…It is especially apposite in cases of acute fulminant disease of the colorectum (Martland and Shepherd, 2007). To avoid the indiscriminate use of IC/IBDU, and to conquer the diagnostic obstacles, a combination of clinical presentation, endoscopic appearance, radiology, histology, surgical findings, and even serologic testing is advocated.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially apposite in cases of acute fulminant disease of the colorectum (Martland and Shepherd, 2007). To avoid the indiscriminate use of IC/IBDU, and to conquer the diagnostic obstacles, a combination of clinical presentation, endoscopic appearance, radiology, histology, surgical findings, and even serologic testing is advocated.…”
Section: Discussionmentioning
confidence: 99%
“…93 Several outcome studies suggested that most IC cases behave like UC. 88,91 Furthermore, the overall pouch failure rate in IC (20%) is closer to UC (10%) than to CD (30%-60%). Conversely, many presumed IC cases with severe pouch complications turn out to be CD.…”
Section: Clinical Relevance and Outcomementioning
confidence: 99%
“…Therefore, it is generally accepted that IC is probably UC; thus, patients with IC should not be denied a restorative procedure if there is no convincing evidence of CD. 17,88,91 A recent microRNA study of IC provided direct molecular evidence that the mRNA profile of IC clustered with that of UC. …”
Section: Clinical Relevance and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Based on clinical, radiological, endoscopic and histological characteristics, is classified as: Crohn's disease (CD), ulcerative colitis (UC) and Indeterminate Colitis (IC). The inclusion of this third category is the fact that 10% to 15% of patients did not have specific macro and microscopically well defined [1,2].…”
Section: Intestinal Inflammatory Processesmentioning
confidence: 99%